Extreme in Sulphur Dioxide Concentration in the Planetary Boundary Layerin Southern South América - Comparison of Mega Cities - Nunes, Mateus Dias; Mariano, Glauber Lopes; Mariano, Ericka Voss Chagas (Anuário do Instituto de Geociências, 2016)
In this study the value of the sulfur dioxide (SO2) total column was assessed, to some of the major metropolitan areas of southern South America (Porto Alegre, Montevideo, Buenos Aires), using data from the sensor OMI (Ozone Monitoring Instrument) for the period 2005-2012. Their annual and monthly variations were investigated using the 99% percentile (P99) for the maximum daily values of the SO2 total column in the planetary boundary layer (PBL). Among the regions analyzed, Montevideo had the highest value of P99 reaching 4,90 DU, being the region more contaminated by SO2 of southern South America. The histograms indicate that the highest frequencies for the three regions analyzed are given in the first four classes of intervals. It was observed increasing values of trend line in the dispersion of the data for the three regions for the same period analyzed.